Análise de grandes eventos na cidade do Rio de Janeiro usando dados de telefonia celular - José, Fernanda Franco Dias (2015)
Mobile data is a valuable tool to analyze the behavior of the urban population, since information about people’s mobility is difficult to obtain. It could provide estimates regarding the displacement and occupation of the population in public areas, helping to develop urban planning measures more specific and efficient. In order to examine the movement around the city of Rio de Janeiro on days of major events, we propose a methodology in order to identify aspects of these events that alow us to know its audience and offer solutions for planners regarding strategies for the organization and security for the event goers. Key-words: urban mobility. CDR data. public events. Rio de Janeiro